Election Law Challenges in the Digital Era - Gunawan - Nachrawi; Rahmat Dwi Putranto (Faculty of Law, Universitas Pekalongan, 2022)
There are many benefits that can be gained from the digitalization process, but there are still many problems that exist in Indonesia. The discourse on digitizing election law enforcement is still a matter of debate. For this reason, it must be studied seriously and actually implemented. Researchers analyze based on normative juridical studies related to digitalization problems and offer solutions to overcome obstacles to digitalization of elections and law enforcement. The advancement of science and technology has both beneficial and detrimental effects on human existence. Similarly, the legal metanarrative must confront the reality of cyberspace as one of the technological advancements. A novel and all-encompassing strategy is required to solve legal metanarratives' helplessness in the face of digital obstacles.